2015
DOI: 10.1002/14651858.cd010269.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2 agonists for long-term sedation during mechanical ventilation in critically ill patients

Abstract: Alpha-2 agonists for long-term sedation during mechanical ventilation in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
4
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 91 publications
4
88
4
7
Order By: Relevance
“…A recent Cochrane meta-analysis pooled seven randomized controlled trials comparing sedation with dexmedetomidine to benzodiazepines, propofol, or “standard care” which included propofol or midazolam. 67 The risk of delirium was numerically lower with dexmedetomidine but not statistically significant (risk ratio [RR] 0.85; 95% confidence interval [CI] 0.63 to 1.14). Subgroup analyses showed the risk of delirium was lower in patients receiving dexmedetomidine than in those receiving benzodiazepines (RR 0.81; 95% CI 0.59 to 1.09; 1007 participants) or propofol (RR 0.37; 95% CI 0.16 to 0.87; 495 participants).…”
Section: Delirium Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Cochrane meta-analysis pooled seven randomized controlled trials comparing sedation with dexmedetomidine to benzodiazepines, propofol, or “standard care” which included propofol or midazolam. 67 The risk of delirium was numerically lower with dexmedetomidine but not statistically significant (risk ratio [RR] 0.85; 95% confidence interval [CI] 0.63 to 1.14). Subgroup analyses showed the risk of delirium was lower in patients receiving dexmedetomidine than in those receiving benzodiazepines (RR 0.81; 95% CI 0.59 to 1.09; 1007 participants) or propofol (RR 0.37; 95% CI 0.16 to 0.87; 495 participants).…”
Section: Delirium Preventionmentioning
confidence: 99%
“…Subgroup analyses showed the risk of delirium was lower in patients receiving dexmedetomidine than in those receiving benzodiazepines (RR 0.81; 95% CI 0.59 to 1.09; 1007 participants) or propofol (RR 0.37; 95% CI 0.16 to 0.87; 495 participants). 67 Overall, the authors found high rates of heterogeneity between the studies, including the baseline risk for delirium, time in ICU prior to enrollment and assessment, frequency and duration of delirium assessments, and levels of sedation targeted, all of which would bias delirium outcomes. They recommended that further studies stratify randomized patients based on delirium risk.…”
Section: Delirium Preventionmentioning
confidence: 99%
“…Gabapentin, klonidin, deksmedetotimidin gibi bazı ilaçların uyku üzerine pozitif etkileri olduğu söylenmesine rağ-men yoğun bakım hastalarında yeterli veri yoktur. Dexmedetomidinin kritik hastalarda mekanik ventilasyon süresi ve yoğun bakım süresini azaltmakla birlikte deliryum üzerine etkisi farklı bulunmamıştır (42).…”
Section: İlaçlar Ve Uykuunclassified
“…The α 2 agonists have been of intense interest in the pediatric critical care literature as sedative agents . An alternative mechanism of action to opioids and benzodiazepines makes them attractive to clinicians.…”
Section: Introductionmentioning
confidence: 99%